THE INFLUENCE OF POSTPARTUM MOTHERS' KNOWLEDGE ON THE INCIDENCE OF BREAST MILK ENGORGEMENT IN BATAM CITY - Prasida Yunita (PT. Radja Intercontinental Publishing, 2026)
For a mother, giving birth to baby is a very happy event as well as a heavy event, full of challenges and anxiety. Problems that occur during breastfeeding include blockage of the milk ducts which causes pain, fever, palpable red breasts, painful lumps or swelling and hardened breasts, also known as breast milk dams. In mothers who experience breast milk dams, breastfeeding will be hampered because the mother feels pain and pain in the breast so that the mother is afraid or lazy to breastfeed. The purpose of this study was to determine how postpartum mother's knowledge about breastfeeding techniques with the incidence of breast milk dam. This research is a cross sectional study, the research site is in PMB X Batam City, the research population is postpartum mothers. Sampling was carried out using a total sampling technique, the number of samples was 85 respondents, the instrument used was a questionnaire in the form of a checklist sheet that had been tested for validity, namely chi-square analysis. The results obtained showed a good knowledge of 31.7%, who experienced breastfeeding dams 71.8% The results of statistical tests with Chi-Square obtained p value = 0.000 <0.05 it can be concluded that Ho is rejected, meaning that there is a relationship between knowledge of postpartum mothers About Breastfeeding Techniques With the Incidence of Breast Milk Dams. Suggestions to improve services for mothers and babies from pregnancy to breastfeeding.